Harm reduction in the time of COVID-19: Case study of homelessness and drug use in Dublin, Ireland - O'Carroll, Austin (Int J Drug Policy, 2021)
Dublin appears to have performed very well as compared to various scenarios for COVID-19 mortality amongst homeless and drug using populations. The experience, if borne out by further research, provides important lessons for policy discussions on the pandemic, as well as broader lessons about pragmatic responses to these key client groups irrespective of COVID-19. The overarching lesson seems that when government policy is well coordinated and underpinned by a science-driven and fundamentally pragmatic approach, morbidity and mortality can be reduced. Within this, the importance of strategic clarity and delivery, housing, lowered thresholds to methadone provision, Benzodiazepine (BZD) provision and Naloxone availability were key determinants of policy success. Further, this paper argues that the rapid collapse in policy barriers to these interventions that COVID-19 produced should be secured and protected while further research is conducted.